2019
DOI: 10.1182/blood.2019898114
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine depletion targets leukemia stem cells through inhibition of electron transport complex II

Abstract: We have previously demonstrated that oxidative phosphorylation is required for the survival of human leukemia stem cells (LSCs) from patients with acute myeloid leukemia (AML). More recently, we demonstrated that LSCs in patients with de novo AML rely on amino acid metabolism to drive oxidative phosphorylation. Notably, although overall levels of amino acids contribute to LSC energy metabolism, our current findings suggest that cysteine may be of particular importance for LSC survival. We demonstrate that exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 13 publications
3
91
0
Order By: Relevance
“…All these proteins can affect redox activity in mitochondria ( Yin et al, 2012 ). The redox state of mitochondria can regulate energy metabolism via the oxidization of several metabolic enzymes, including aconitase, α-ketoglutarate dehydrogenase (α-KGDH), malate dehydrogenase ( Reed et al, 2008 ), and succinyl-CoA-3-oxoacid CoA transferase (SCOT) ( Garcia et al, 2010 ), and complexes I ( Cortes-Rojo et al, 2020 ), II ( Jones et al, 2019 ), and V ( Kramer et al, 2018 ). It can also regulate S-glutathione glycosylation, a modification that reflects the redox state of mitochondria by reversibly forming mixed disulfide bonds between protein cysteine sulfhydryl and GSH ( Schafer and Buettner, 2001 ; Hill and Bhatnagar, 2012 ).…”
Section: Tca Cycle and Oxphos Deficitsmentioning
confidence: 99%
“…All these proteins can affect redox activity in mitochondria ( Yin et al, 2012 ). The redox state of mitochondria can regulate energy metabolism via the oxidization of several metabolic enzymes, including aconitase, α-ketoglutarate dehydrogenase (α-KGDH), malate dehydrogenase ( Reed et al, 2008 ), and succinyl-CoA-3-oxoacid CoA transferase (SCOT) ( Garcia et al, 2010 ), and complexes I ( Cortes-Rojo et al, 2020 ), II ( Jones et al, 2019 ), and V ( Kramer et al, 2018 ). It can also regulate S-glutathione glycosylation, a modification that reflects the redox state of mitochondria by reversibly forming mixed disulfide bonds between protein cysteine sulfhydryl and GSH ( Schafer and Buettner, 2001 ; Hill and Bhatnagar, 2012 ).…”
Section: Tca Cycle and Oxphos Deficitsmentioning
confidence: 99%
“…We focused on IRE1α and PERK, well-known participants in inducing apoptosis. Indeed, PERK has been shown to inhibit the translation initiation factor 2α (eukaryotic initiation factor 2 alpha (eIF2α) by phosphorylation, thereby, reducing protein synthesis and overload [ 23 , 24 , 25 ]. In accordance, our results revealed rapid phosphorylation of eIF2α in MV-4-11 cells within 15 min following VAS3947 exposure ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…AML cells have an abundant expression of proteins implicated in the GSH system [ 23 ] and are highly sensitive to drugs targeting GSH metabolism [ 23 ]. Interestingly, the use of an enzyme that degrades cysteine, a precursor for the synthesis of GSH, completely eradicates leukemic stem cells (LSCs) without any effect on normal hematopoietic stem/progenitor cells [ 24 ]. Indeed, the authors showed that the survival of ROS low LSCs is dependent on the availability of cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they displayed an enrichment in gene signatures related to leukemic stem cells, cysteine metabolism or mitochondria ( Supplementary Fig. S1H-S1J), all known markers of response to either VEN or VEN+AZA 25,[45][46][47] . Finally, transcriptomes of VEN-resistant AML patients are enriched in gene sets related to hypoxia and glycolysis.…”
Section: Oxphos-dependent Resistance Of Aml Cells To Cytarabinementioning
confidence: 99%